New-onset metabolic syndrome is associated with accelerated renal function decline partially through elevated uric acid: an epidemiological cohort study - Xu, Qiuyu; Fan, Xiaohong; Chen, Gang; Ma, Jie; Ye, Wenling; Ai, Sanxi; Wang, Li; Zheng, Ke; Qin, Yan; Chen, Limeng; Li, Mingxi; Li, Xuemei (Frontiers in Endocrinology, 2024)
Background The burden of metabolic syndrome (MetS) continues to rise globally and is associated with complications of multiple organ systems. We aimed to identify the association between changes in MetS status and accelerated renal function progression through a regional epidemiological survey in China, thus discovering influence factors with treatable potential. Methods This study was a population-based survey conducted in 2008 and 2014, assessing a representative sample of 5,225 individuals from rural areas of China. They were divided into four subgroups according to their MetS status in 2008 and 2014 (Never, Previously abnormal, New-onset, and Consistent). Multivariate logistic regression and stratification analysis evaluated the relationship between clinical factors and renal function decline under different MetS statuses. Smooth curve fitting further addressed the role of serum uric acid, illustrating the vital turning point of uric acid levels in the background of renal function deterioration. Results Of all groups of MetS states, the new-onset MetS showed the most significant eGFR decline, with a 6.66 ± 8.21 mL/min/1.73 m2 decrease over 6 years. The population with newly-onset MetS showed a considerable risk increase in delta eGFR with a beta coefficient of 1.66 (95%CI=1.09-2.23) after necessary correction. In searching for the drivers, the strength of the association was significantly reduced after additional adjustment for uric acid levels (β=0.91, 95%CI=0.35-1.45). Regarding the turning point, uric acid levels exceeding 426 μmol/L were more significantly associated with the stepped-up deterioration of kidney function for those with new-onset MetS. Conclusions Metabolic syndrome demonstrated a solid correlation with the progression of renal function, particularly in those with newly-onset MetS status. In addition to the diagnostic components of MetS, hyperuricemia could be used as a marker to identify the high risk of accelerating eGFR decline early. Furthermore, we suggested a potential renal benefit for the newly-onset MetS population when maintaining their serum uric acid level below the criteria for asymptomatic hyperuricemia.